2016
DOI: 10.1002/nbm.3495
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility‐based time‐resolved whole‐organ and regional tissue oximetry

Abstract: The magnetism of hemoglobin – being paramagnetic in its deoxy and diamagnetic in its oxy state – offers unique opportunities to probe oxygen metabolism in blood and tissues. The magnetic susceptibility χ of blood scales linearly with blood oxygen saturation, which can be obtained by measuring the magnetic field ΔB of the intravascular MR signal relative to tissue. In contrast to χ the induced field ΔB is non-local. Therefore, to obtain the intravascular susceptibility Δχ relative to adjoining tissue from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 86 publications
(112 reference statements)
0
65
0
1
Order By: Relevance
“…An acute increase in magnetic susceptibility during the onset of TGA may be due to the increase of blood deoxyhemoglobin. Deoxyhemoglobin is paramagnetic . Paramagnetic substances in tissues cause local susceptibility changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An acute increase in magnetic susceptibility during the onset of TGA may be due to the increase of blood deoxyhemoglobin. Deoxyhemoglobin is paramagnetic . Paramagnetic substances in tissues cause local susceptibility changes.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxyhemoglobin is paramagnetic. 34 Paramagnetic substances in tissues cause local susceptibility changes. A recent study showed that the susceptibility value in the prominent cortical veins in the stroke hemisphere was significantly higher than that in the contralateral hemisphere and in healthy controls and in the meantime, the oxygen saturation in the prominent cortical veins was decreased, ranging from 16% to 44% relative to the veins of the contralateral hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Flow‐compensated QSM sequences can be used not only to visualize veins, but also to measure venous susceptibility , which can be used to noninvasively calculate venous oxygen saturation level, SvO 2 . SWI is very useful for its detailed depiction of veins, but the vein signal intensity on SWI (as well as on T 2 and T 2 *) varies both with the vein orientation and with echo time, and the underlying venous oxygenation cannot be derived .…”
Section: Other Clinical Uses Of Qsmmentioning
confidence: 99%
“…Magnitude modeling methods include quantitative imaging of extraction of oxygen and tissue consumption (QUIXOTIC), calibrated fMRI, and quantitative BOLD (qBOLD) . Phase modeling methods have been used for whole brain CMRO 2 measurements . Building on this, quantitative susceptibility mapping (QSM) enables generation of CMRO 2 maps .…”
Section: Introductionmentioning
confidence: 99%